Relationship between Psychological Distress and Perceived Stigma on Mental Well-Being in People with Epilepsy: Self-Compassion as a Moderator - ألابي، أولاديخو تسليم; موسباو، لوال أبيودون; ووجوتاري، أجيلي كيني; أبيولا، ساكا سعيد; شيوما، أوتوغيلي ثقة (اتحاد الاطباء النفسانيين العرب, 2023)
غاية: درس البحث العلاقة بين التعاطف الذاتي، وصمة العار المتصورة، والضيق النفسي والرفاه العقلي بين الأشخاص الذين يعانون من الصرع، وكذلك التحقيق في الدور المعتدل في التصنيف الذاتي على علاقة وصمة العار المتصورة مع البئر العقلي بين الأشخاص الذين يعانون من الصرع طرق: اعتمدت البحث تصميم المسح. عينة مريحة من 200 (59.1% من الذكور * 40.9 % من الإناث) مرضى الصرع الذين كانوا يحضرون عيادة المتابعة في وحدة علم الأعصاب المركز الطبي الفيدرالي، لوكوجا تتراوح أعمارهم بين 18 و59 سنة M=36.75)، (SD=10.95 تم جمع بيانات هذه الدراسة باستخدام مقياس التعاطف الذاتي في (NEFF (SCS من أجل التعاطف الذاتي، ومقياس الضيق النفسي Kessler (10) من أجل النطاق النفسي، وصمة العار من الصرع (SSE) للوصمة المتصورة وWarwick Edinburgh Mental الرفاهية (WEMWBS) للرفاه العقلي. وقد تم تحليل البيانات من خلال تصحيح بيرسون المتعدد وكذلك النموذج 1 من الماكرو لعملية الاعتدال. تم تنفيذ التحليلات مع Process Marco لـ IBM SPSS الإصدار 25.0 نتائج: أظهرت النتائج وجود علاقة كبيرة بين التعاطف الذاتي والرفاه العقلي (ص) = 0.250). كشفت نتائج الدراسة كذلك عن وجود علاقة كبيرة بين الضيق النفسي والرفاه العقلي (ص) = 293)، وهناك علاقة كبيرة بين وصمة العار المتصورة والرفاه العقلي (ص = 0.320). كشفت النتائج عن العلاقة المباشرة التعبيرية بين وصمة العار المتصورة والرفاه العقلي وكشفت كذلك أن التصنيف الذاتي يعدل بشكل كبير العلاقة المباشرة بين وصمة العار المتصورة والرفاه العقلي الخلاصة: ترتبط وصمة العار المتصورة والتعاطف الذاتي بالرفاه العقلي والتجمع الذاتي قد تلعب دورا مهما في العلاقة بين وصمة العار المتصورة والرفاه العقلي بين الأشخاص الذين يعيشون مع الصرع. Objective: The current research examined the relationship between self compassion, perceived stigma, psychological distress and mental well-being in people with epilepsy. It also investigated the moderating role of self-compassion on perceived stigma relationship with mental-well-being. Methods: Using a survey design, a convenience sample N=200 (59.1% men; 40.9% women) patients diagnosed with epilepsy who were attended a follow-up clinic in the neurology unit, Federal Medical Centre, Lokoja aged 18 to 59 years (M=36.75, SD=10.95). The data for this study was collected using the Neff’s Self-Compassion (SCS) scale for self-compassion, The Kessler Psychological Distress Scale (K10) for psychological distress, the distress stigma scale of Epilepsy (SSE) for the perceived stigma and Warwick Edinburgh Mental Well Being Scale (WEMWBS) for men well-being. Data were analyzed through Pearson multiple correction as well as model 1 of moderation Process macro. The analyses were executed with PROCESS Marco for IBM/SPSS version 25.0 Results: The results showed a significant correlation between self-compassion and mental well-being (r =.250). The study results further revealed significant correlation between psychological distress and mental well-being (r = 293), and there is significant correlation between the perceived stigma and mental well-being (r =.320). The results revealed expressive direct relationship between perceived stigma and mental well being and further revealed that self-compassion significantly moderates direct relationship between perceived stigma and mental well-being. Conclusion: perceived stigma and self-compassion is associated with mental well-being and self-compassion may play important role on the relationship between perceived stigma and mental well being among persons living with Epilepsy.
Keywords: الاضطرابات النفسية -- الضيق النفسي -- الصحة العقلية -- مرض الصرع